CHALLENGES OF SMART TOURISM IN MALAYSIA ECO-TOURISM DESTINATIONS - Ab. Rahman, Syakir Amir; Dura, Nur’Hidayah; Yusof, Muhamad Asrah; Nakamura, Hitoshi; Abu Nong, Rahmat (PLANNING MALAYSIA, 2020)
Smartness helps in transferring and sharing information to facilitate tourism industry optimizing performance and competitiveness, generating solution for asset evaluation and shaping tourism products and services in a real-time. In Malaysia, tourism industry is moving forwards to acknowledge smart tourism concept as Malaysia Smart Tourism 4.0 initiatives is launched recently. Therefore, this study aims to identify challenges of smart tourism application in Malaysia. 400 respondents among domestic and international tourists were recruited for the study, using questionnaire survey in two eco-tourism destination, Pulau Langkawi and Cameron Highland. Chi-square test was used to assess the challenges. Awareness, security and privacy, and implementation mechanism of smart tourism are among the highest challenges were observed. This study extends for a new establishment of proper and comprehensive framework of smart tourism in Malaysia.